Assessment of food insecurity and its correlates in a rural community of Karnataka: a case study - Jacob, Ankeeta Menona; Rajaram, Dinesh; Manjunath, Bhanu; Kunnavil, Radhika (International Journal Of Community Medicine And Public Health, 2018)
Background: Food insecurity exists when people are undernourished due to the physical unavailability of food, lack of social or economic access to adequate food, and inadequate food utilization. As per FAO, India is home to 25% of world’s hungry population and 194.6 million undernourished people for the period of 2014-2016. The objectives were to assess the food insecurity and determine its correlates in a rural community of Karnataka. Methods: A cross sectional study was undertaken to assess food insecurity and its correlates in households of a rural community of Karnataka using the “Household Food Insecurity Access Scale (HFIAS) for measurement of food access: Version 3” questionnaire during December 2014. The data collected was analyzed using SPSS version 20.0 and mean, proportion and chi-square were calculated as appropriate. Results: The average HFIAS score was as low as 4.15. 80.8% of the 52 households were food insecure, of which 17.3% were mildly insecure, 48.1% were moderately insecure and 15.4% were severely food insecure. Conclusions: With 80.8% food insecurity in the rural agriculture-based community, there is a need for improvements in stability, accessibility and utilization of available food through use of fair price shops and garden kitchen promotion.